Estimating glutamate and Glx from GABA-optimized MEGA-PRESS: Off-resonance but not difference spectra values correspond to PRESS values - Maddock, Richard J.; Caton, Michael D.; Ragland, J. Daniel (Psychiatry research. Neuroimaging, 2018)
•Glutamate can be measured two ways during a GABA-optimized MEGA-PRESS scan.•These glutamate measurements have not been directly compared to conventional methods.•MEGA-PRESS off-resonance glutamate values correspond well to PRESS values.•MEGA-PRESS difference spectra glutamate values correspond poorly to PRESS values.•MEGA-PRESS off-resonance glutamate values can serve as a proxy for PRESS values. Proton magnetic resonance spectroscopy measurements of glutamate and GABA are important in neuropsychiatric research. Some study designs require simultaneous measurement of both metabolites. GABA measurement requires specialized pulse sequences, the most common approach being J-difference spectral editing with MEGA-PRESS. This method enables two different strategies for concurrently measuring glutamate - from either off-resonance or difference spectra. However, it is uncertain how either strategy compares to conventional glutamate measurements. Here we compared these approaches in 49 subjects (28 healthy volunteers and 21 first-episode psychosis patients), in whom both PRESS (TE 80) and MEGA-PRESS (TE 68) spectra were obtained from dorsolateral prefrontal cortex. Glutamate and glx estimates from MEGA-PRESS difference and off-resonance spectra were compared to glutamate and glx estimates from PRESS spectra using correlational analyses. In healthy volunteers, correlations between PRESS and MEGA-PRESS off-resonance values were r ≥ 0.88 and were significantly higher than correlations between PRESS and MEGA-PRESS difference spectrum values (r ≤ 0.36). Patients showed a similar pattern. Lower correlations with difference spectrum values may reflect a disproportionate impact of field instabilities on co-edited glutamate signals. The results suggest that MEGA-PRESS off-resonance spectra can substitute for separately-acquired PRESS spectra in studies requiring simultaneous glutamate and GABA measurements. [Display omitted]